THE IMPACT OF DIGITAL MARKETING ON PILGRIMAGE TOURISM DEVELOPMENT IN UZBEKISTAN (International Educators Conference, 2025)
This article discusses ways to develop tourism in Uzbekistan, as well as many digital advertising methods used to attract tourists to Uzbekistan. The article analyzes static data, examines different forms of digital advertising, and gives key recommendations for using digital advertising to increase the number of tourists visiting Uzbekistan.